Direct but Unintentional Killing: The Debate between Rhonheimer and Guevin’s Conception of the Object of Moral Choice - Joyce, David (Studia Bioethica, 2015)
Any human act, i.e. any act that is not a so called ‘act of man’ , is done because there is some aim in mind, even were it simply to avoid something you don’t want to start. Your reason or end in acting is some good in light of which you act . Among ethicists there are different opinions about the role of intentionality in analyzing the human act and its relation to determining what the object of your act is. This paper will examine whether what you do is tantamount to what is intended. Clarity becomes critical when you have an instance of what Rhonheimer has called ‘vital conflicts’. While there might be something you intend and desire as the end in your acting, sometimes there will be many resulting effects which are not desired. This raises the question whether some undesired ends or results must necessarily also inform your choice and are therefore determinative of what you do.